Sharia Banking Strategy in Increasing MSME Entrepreneurship in Muara Tebo - Savitri, Silvia; Mezaluna, Dewi; Isamuddin, Isamuddin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This research highlights the important role of micro businesses as an economic support for the people of Muara Tebo who are still facing limited capital, technology, market access, and managerial capabilities. The purpose of the study is to analyze the contribution of Sharia Banks, especially BSI KCP Muara Tebo, in improving the entrepreneurship of micro business actors through financing and business empowerment. This field research uses a descriptive qualitative approach with data sources from banks, micro business actors, and supporting informants. Data was collected through in-depth interviews, observations, and documentation, then analyzed with thematic methods and tested for validity through triangulation of sources and techniques. The results of the study show that Sharia Banks play a significant role through murabahah financing, business consulting, educational seminars, and business development. The impact can be seen in increasing working capital, production capacity, sales volume, income, and confidence of business actors, while reducing dependence on loan sharks. Some businesses are even able to increase the workforce, expand the scale of operations, and open up opportunities for expansion. However, strengthening Islamic financial literacy and local needs-based assistance still needs to be improved so that community economic empowerment is more inclusive, sustainable, and effective.